ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA BADAN USAHA MILIK DESA UNTUK MEWUJUDKAN GREEN ACCOUNTING (STUDI KASUS DI DESA MAYANGAN KECEMATAN GUMUKMAS KABUPATEN JEMBER) - Achmad Munir; Abdul Wahid Mahsuni; Siti Aminah Anwar (Universitas Islam Malang, 2021)
Nowadays environmental problems are one of the things that must be paid attention to by the community, especially for companies or business people who often pollute the environment from their production activities. Therefore, the Company as part of people's lives must participate in preserving the environment. This participation certainly costs money, so there must be recognition, disclosure, and presentation in the company's accounting records, to create green accounting and a healthy environment. The purpose of this research is to find out how to apply environmental accounting to village-owned enterprises in Mayangan Village, Gumukmas District, Jember Regency, to find out how to record, report and present environmental accounting on village-owned enterprises in Mayangan Village, Gumukmas District, Jember Regency, to provide knowledge to village-owned enterprises in Mayangan Village, Gumukmas District, Jember Regency regarding the functions and benefits of green accounting. This research uses a qualitative descriptive method. The data used in this study are primary and secondary data obtained from interviews, observations, and documentation, then the data is analyzed to draw conclusions. for recording environmental accounting reports.Keywords: Environmental Accounting, Village Owned Enterprises, Green Accounting